The Legal Protection of Fishermen Sales in Dealing for Fishery Results in Sibolga - Ramlan Ramlan; Chandra Argawansyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to provide legal protection to tenant fishermen in the agreement for fisheries products between owner fishermen and tenant fishermen in Sibolga. The research used is a merger of legal research and social research (mix method), using a legislative approach and descriptive explorative approach. Data is collected through primary data and secondary data, and analyzed qualitatively and quantitatively. Based on the results of the study that the agreement for the sharing of fisheries between the owner's fishermen and fisherman cultivators in the City of Sibolga conducted unwritten this is considered a hereditary habit. The start of the agreement begins with an invitation to ABK regarding when to leave for sea, while the end of the agreement occurs when there is a distribution of wages received by ABK. In the production sharing agreement, the owner's fisherman gets 90% while the sharper fisherman gets a 10% share. Because there are no written rules regarding fisheries yield sharing agreements, if there is a dispute between the owner's fishermen and the HNSI cultivating fishermen who act as mediators to resolve the problem in good faith between the two parties.